On the history of medicine in the United States, theory, health insurance, and psychiatry: an interview with Charles Rosenberg - Charles Rosenberg; Rafael Mantovani (História, Ciências, Saúde: Manguinhos)
Abstract An interview with Charles Rosenberg conducted by Rafael Mantovani in November 2013 that addressed four topics. It first focused on the way in which Rosenberg perceived trends and directions in historical research on medicine in the United States during the second half of the twentieth century. The second focus was on his experience with other important historians who wrote about public health. Thirdly, he discussed his impressions about the current debate on health policy in his country. Finally, the last part explores some themes related to psychiatry and behavior control that have appeared in a number of his articles.